2021
DOI: 10.1002/capr.12390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a combined intervention targeting at‐risk post‐secondary students: When it comes to graduating, mental health matters

Abstract: The transition to post-secondary can be onerous for many students, often fraught with challenge across one or multiple domains: academic, social, physical and mental health, financial and developmental.In recent decades, reports of mental distress among post-secondary students have been increasing dramatically (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
(74 reference statements)
2
6
0
Order By: Relevance
“…This programme is unique in its focus on the therapeutic relationship in delivering academic support and promoting psychological well‐being. Results of these studies confirmed that the intervention was linked to an increase in psychological wellness and overall academic performance and academic functioning in students with differential needs and was thus identified as a promising two‐pronged approach to promoting student academic success and retention (Antunes‐Alves & Langmuir, 2021; Bilodeau & Meissner, 2016).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…This programme is unique in its focus on the therapeutic relationship in delivering academic support and promoting psychological well‐being. Results of these studies confirmed that the intervention was linked to an increase in psychological wellness and overall academic performance and academic functioning in students with differential needs and was thus identified as a promising two‐pronged approach to promoting student academic success and retention (Antunes‐Alves & Langmuir, 2021; Bilodeau & Meissner, 2016).…”
Section: Introductionmentioning
confidence: 68%
“…Student counselling initiatives may play an important role in mediating the effects of these factors. Indeed, recent research has begun to provide evidence in support of their effectiveness for reducing psychological distress and positively impacting academic performance and retention (Antunes‐Alves & Langmuir, 2021; Biasi et al., 2017; Bilodeau & Meissner, 2016; McKenzie et al., 2015). While recent studies have begun to solidify the evidence for the effectiveness and importance of student counselling initiatives on student mental health and academic performance, studies have been limited to primarily pre‐ to post‐methodological designs and still little is known regarding the mechanisms by which these positive changes occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing so may open opportunities for all genders to have equitable experiences, develop wellrounded skill sets, and pursue interests that spark their passions as unique individuals. T he typical age range of college students (18-25) is when most individuals first experience distress due to a mental healthrelated concern (Antunes & Langmuir, 2021). In fact, almost 15-23% of college students with mental health problems have said their disorders have negatively impacted their academic performance (Bruffaerts et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In most colleges and universities, the way to study and judge the psychological state of college students is still relatively traditional, lacking efficiency and accuracy (Antunes-Alves et al, 2021). The traditional psychological intervention methods mostly adopt a psychological questionnaire screening, lectures and post psychological treatments.…”
Section: Introductionmentioning
confidence: 99%